ANALISIS PENGARUH SUDUT BEVEL DAN POLARITAS TERHADAP DEFECT PADA TEMBUSAN HASIL PENGELASAN SMAW - Novansyah, Fauzan; Ihsan Rijal, Maulana; Yhuto Wibisono Putra, Ananda; Aryaguna, Rasendriya; Yuga Pranata, Ridwan (KURVATEK, 2023)
SMAW (Shielded Metal Arc Welding) is one of the most frequently used welding methods in industry. One of the causes that affect the quality of SMAW welding Results is the bevel angle and polarity used. The research method used in this study is an experiment with a qualitative approach. This study aims to explore and analyze the effect of bevel angle and polarity on defects in SMAW welding translucent. The Results show that specimens with positive polarity (DCEP) produce more defects in the weld penetration than those with negative polarity (DCEN), both in terms of quality and quantity. then an analysis of the variation of the angle used can be seen that an angle of 30° produces better weld penetration Results in terms of quality and quantity. so as to minimize defects in the Results of weld penetration the recommended parameters that can be used are a bevel angle of 30° and negative polarity (DCEN).